A few aspects of early nineteenth-century village economies: Taxation and ground rents - Asdrachas, Spyros (The Greek Review of Social Research, 1981)
This survery presents some examples of village economies in early nineteenth century Greece. What ground rents and cereal crops are composed of, the sizes of grazing grounds, the taxation effects on the villages' economy and demography, the peasants' debts—a corol lary of fiscal and/or monetary ground rents—such are the main axes of this study combining qualitative evidence with a few quantitative estimates established from taxation data.